Protagonist’s Self-Writing: Modus of Biography at the Intersection of Methodologies - Yulia Pavlenko (Pitannâ Lìteraturoznavstva)
The article views the place of the fictional subject’s self-writing at workshops concerning autobiographical questions. The study reveals the repression of a particle “grafos” in the formula “auto-bio-graphy” and leads to the idea of the compensatory function of the self-writing practice analysis in that very situation. The change of the perspective on the research of self-writing appeals to the problematic of the method. The fictional subject’s self-writing represents a field of multiple crossings of different methodologies that examine ego-documents; therefore in this field the role of figures and metaphors is actualized. It is quite logical to describe the self-writing practice within the coordinates of the critical synthesis as the place of illustration and transmission of the values, as the dimension of self-reflectiveness, multi-generic reflectiveness, introspection, representation of author/reader relations, display of intertextuality (both declared by the author and unforeseen), play in autobiography, tension between fiction and reference. The fictional subject’s self-writing is not identical to the autobiographical writing of a real subject, though a lot of semantic fields and registers come across. The character writing the story of his life becomes that another who makes it possible to multiply the experience of the inner harmony research, to see the power of the writing work from one side approaching thus to its ontology. The key for understanding the figure of this another is deeply hidden in the interpretation of the fictional space metaphoric.